Integrating univariate niche dynamics in species distribution models: A step forward for marine research on biological invasions. (30th December 2019) - D'Amen, Manuela; Azzurro, Ernesto
Abstract: Aim: The development of approaches to predict the distribution and potential expansion of invasive species is still an open challenge. Here our goal is to improve the modelling procedure for marine invaders by coupling Species Distribution Models (SDMs) with an analysis of their univariate niche dynamics. In particular, we tested for the first time whether choosing model predictors among the stable niche dimensions was effective in improving predictions of invasive species expansion. Location: Mediterranean Sea. Taxon: Dusky spinefoot, Siganus luridus . Methods: We analysed the univariate niche dynamics for S. luridus across its native and invaded ranges, by applying a standardized framework that allowed the identification of cases of niche stability or shift. We compared inter‐range transferability of SDMs fitted with different combinations of labile or stable predictors. Finally, we evaluated interactions in SDM settings (calibration area, model technique and predictors set) on models' predictive ability, using independent data from the most recent phase of invasion. Results: We detected a pattern of niche stability for several variables, especially salinity and bathymetry, which positively influenced model inter‐ranges transferability: when the models calibrated in the native range include only stable niche axes, predictive ability is improved. We also identified a shift towards lower surface temperatures in the introduced range, which were almost never experienced by the species before invasion. The model calibrated within the combined ranges was the most ecologically congruent. Also, models calibrated in the invaded range allowed a correct prediction of range expansion, with the predicted suitable areas only slightly underestimated. Main conclusions: We provide the first evidence that using conserved predictors in SDMs improves inter‐range projections of expanding invasive species. Variable selection, calibration area and modelling technique all matter when modelling invasive species, with important interaction effects. We provide guidelines on how to improve SDMs applications in biological invasion research.